Plants' native distributions do not reflect climatic tolerance. Issue 6 (25th February 2016) - Bocsi, Tierney; Allen, Jenica M.; Bellemare, Jesse; Kartesz, John; Nishino, Misako; Bradley, Bethany A.
Abstract: Aim: Biogeographers have long known that plant species do not fully encompass their fundamental niche. Nonetheless, in practice, species distribution modelling assumes that plant distributions represent a reasonable approximation of their environmental tolerance. For ecological forecasting, projections of habitat loss due to climate change assume that many species will be unable to tolerate climate conditions outside of those found within their current distributional ranges. We aim to test how well occurrences in the native range approximate the climatic conditions in which plant species can survive. Location: Continental USA. Methods: We compared the climatic conditions between occurrences in the US native versus US non‐native ranges using 144 non‐invasive plant species. We quantified differences in January minimum temperature, July maximum temperature and annual precipitation as indicators of climatic tolerance. We also compared modelled potential distributions throughout the US based on native and total ranges to test how expanded climatic tolerance translates into predicted geographical range. Results: Most species (86%) had non‐native occurrences in climates outside those described by their native distributions. For the 80 species with lower minimum temperatures at non‐native occurrences, the median expansion of minimum temperature tolerance was −2.9 °C. Similarly, for the 90 species with lower precipitation at non‐native occurrences, the median expansion of minimum annual precipitation was −23 cm. Broader climatic conditions at non‐native occurrences expanded the modelled potential geographical range by a median of 35%, with smaller range species showing larger expansions of potential geographical range. Main conclusions: Our results show that plants' native ranges strongly underestimate climatic tolerance, leading species distribution models to underpredict potential range. The climatic tolerance of species with narrow native ranges appears most prone to underestimation. These findings suggest that many plants will be able to persist in situ with climate change for far longer than projected by species distribution models.